Bio-thermal Herbst application during the mixed dentition period. - (:unkn) unknown (My University, 1994)
As is well known Class II division 1 cases are the most common cases which may be treated by functional therapy. The best treatment time is the peak growth period for such cases which might coincide with mixed dentition usually. Removable functional appliances are used in cooperative patients successfully but they are not indicated in noncooperative and mouth-breathing patients. Biothermal Herbst appliance is such an appliance which may be used as a fixed appliance in the mixed dentition period. The aim of this study was to observe the clinical usage and the effectiveness of Biothermal Herbst appliance with four cases in mixed dentition. At the end of the treatment period, Class II skeletal and dental relationships were transformed to Class I, upper incisors uprighted in all cases and lower incisors proclined in whole except one case.